2013
DOI: 10.1074/jbc.m113.485490
|View full text |Cite
|
Sign up to set email alerts
|

Poxviral Protein A52 Stimulates p38 Mitogen-activated Protein Kinase (MAPK) Activation by Causing Tumor Necrosis Factor Receptor-associated Factor 6 (TRAF6) Self-association Leading to Transforming Growth Factor β-activated Kinase 1 (TAK1) Recruitment

Abstract: Background: Activation of p38 MAPK by poxviral A52 is TRAF6-dependent, but the mechanism is unknown. Results: Disruption of either an identified TRAF6-binding motif or of A52 dimerization prevents TRAF6 oligomerization, TAK1 recruitment, and p38 activation. Conclusion: A52 activates p38 MAPK activation by causing TRAF6 oligomerization, leading to TAK1 recruitment. Significance: This work reveals the molecular basis for poxviral activation of p38 MAPK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Next, to identify the kinases responsible for P62 induction, we focused on P38, which is a downstream kinase activated by TRAF64344. In the present study, we found that IR facilitated P38/P62 activation in livers leading to the accumulation of LC3II and autophagic vacuoles.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Next, to identify the kinases responsible for P62 induction, we focused on P38, which is a downstream kinase activated by TRAF64344. In the present study, we found that IR facilitated P38/P62 activation in livers leading to the accumulation of LC3II and autophagic vacuoles.…”
Section: Discussionmentioning
confidence: 55%
“…LPS-induced ALIS formation is dependent on P62 levels, and knockdown of either of these molecules (such as MyD88, IRAK4, TRAF6) decreases LPS-induced GFP-LC3 + dot formation 22 . Next, to identify the kinases responsible for P62 induction, we focused on P38, which is a downstream kinase activated by TRAF6 43 44 . In the present study, we found that IR facilitated P38/P62 activation in livers leading to the accumulation of LC3II and autophagic vacuoles.…”
Section: Discussionmentioning
confidence: 99%
“…The panels below each graph show that the expression levels of the different proteins were similar, except A49, which was expressed at much lower levels, especially in HeLa cells. Previously, it was reported that A46 inhibits Toll-like receptor/IL-1-stimulated MAPKs and NF-κB activation, whereas A52 can activate p38 MAPK and JNK activity, but whether these Bcl-2-like proteins can also induce AP-1 was not demonstrated ( Bowie et al , 2000 ; 2005 , Stack et al , 2013 ; Stack & Bowie, 2012 ; Maloney et al , 2005 ; Keating et al , 2007 ). B14 was also reported to increase PMA-stimulated AP-1 activity ( Chen et al , 2008 ).…”
mentioning
confidence: 99%
“…For immunoblotting, a total of 30 mg of protein extract was separated on 10% SDS-PAGE gels and transferred to nitrocellulose membranes. For the dimerization studies, cell lysates were analyzed on native (nondenaturing) gels (13). The levels of protein expression were evaluated by Western blot as previously described in detail (14).…”
Section: Immunoblot Analysismentioning
confidence: 99%